The identification and examination of the elements that caused a schism in the Johannine community at the end of the first century CE - Van der Merwe, Dirk (HTS teologiese studies, 2007)
A group of people within the Johannine community (2:18) contributed towards destroying the fellowship of this community. Because 1 and 2 John do not provide direct evidence of the identities of the community’s heretically inclined members, they are defined in different ways by different scholars. A search for socio-religious circumstances which contribute towards determin-ing the opponents and adherents of the author which created the agenda for the reconstruction of the phenomena that caused this schism. The nature of the schism comprises “Pneumatological,” “Christological” and “ethical” issues encoded in the polemical language of slogans, dialectic discourse, confessions and denials. The schism in 1 John proves to be a matter of different interpretations of a shared tradition.